2021
DOI: 10.1016/j.ajhg.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale machine-learning-based phenotyping significantly improves genomic discovery for optic nerve head morphology

Abstract: Genome-wide association studies (GWASs) require accurate cohort phenotyping, but expert labeling can be costly, time intensive, and variable. Here, we develop a machine learning (ML) model to predict glaucomatous optic nerve head features from color fundus photographs. We used the model to predict vertical cup-to-disc ratio (VCDR), a diagnostic parameter and cardinal endophenotype for glaucoma, in 65,680 Europeans in the UK Biobank (UKB). A GWAS of ML-based VCDR identified 299 independent genome-wide significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 77 publications
(120 reference statements)
0
59
0
Order By: Relevance
“…They suggested that genetic variation in VCDR may be mediated by pathophysiologic processes involving IOP and the anterior segment of the eye. In fact, they found that there was a 13% overlap between genes in an IOP GWASA meta-analysis and their new VCDR GWAS [65]. Similarly, proposed molecular mechanisms linking genes to IOP and/or VCDR may have similar pathways, whether through glial activation or inactivation or through alterations in aqueous humor dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They suggested that genetic variation in VCDR may be mediated by pathophysiologic processes involving IOP and the anterior segment of the eye. In fact, they found that there was a 13% overlap between genes in an IOP GWASA meta-analysis and their new VCDR GWAS [65]. Similarly, proposed molecular mechanisms linking genes to IOP and/or VCDR may have similar pathways, whether through glial activation or inactivation or through alterations in aqueous humor dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the AI-enhanced GWAS performed by Alipanahi et al was able to use the AI-enhanced models to calculate genetic/polygenic risk scores (GRS/PRS), a method of quantifying risk based on individualized genetic characteristics. Alipanahi et al calculated a PRS for VCDR that they proposed could be applied to POAG, and they demonstrated that patients with a higher VCDR PRS had a higher prevalence of POAG [65].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations